PELATIHAN PEMBUATAN TEPUNG MOCAF DAN MIE BASAH DI DESA WONOHARJO KECAMATAM WONOGIRI - Siswadi, Efrain Patola & Sarwono (Innofarm:Jurnal Inovasi Pertanian, 2015)
Gapoktan Harjo Kinasih, Village of Wonoharjo, district of Wonogiri, been able to produce of cassava chips good-quality. The chip want further diversified into flour mocaf in order to achieve greater added value. but they are constrained by the limitations of funds of funds for the procurement of flouring machine, sieving, packaging (sealler), and the training to use these machines. Therefore, it is necessary to help overcome these obstacles. Keywords : cassava, diversification, and mocaf